The influence of acculturation strategy and school background on academic performance and adaptation to university - Mosenene, Mamolisana Carlista (My University, 2021)
The Apartheid regime ended 26 years ago, however, the students that were not directly impact by Apartheid continue to suffer its consequences. South Africa’s department of education has succeeded in assisting students from disadvantaged schools to enroll into higher education institutions through funding mechanisms. However, students from disadvantaged schools often face acculturation and adaptation to university challenges. Furthermore, they experience high academic failure and university drop out. The objective of this study was to investigate whether these challenges are due to school background. The overarching aim was to understand student high failure rate and university drop out. This aim was achieved by taking into consideration the four research questions aimed at understanding the relationship between the study variables. The school background is categorized into two types, namely, low quintile school background (quintile 1 to 3) and high quintile school background (quintile 3 to 4). Acculturation strategy was assessed using a measurement created by the researcher incorporating Berry’s model of four acculturation orientations (categories), namely, integration, separation, marginalisation and assimilation (Berry, 1997). The Student Adaption to College Questionnaire (SACQ), developed by Baker and Siryk (1999), assessed adaptation to university. Academic performance was assessed using several indices, including student’s scores on the midyear examination, ratings of their performance and English proficiency. This was a quantitative study, cross-sectional non-experimental research design. The data was analysed using a one-way MANOVA, one-way ANOVAs, across tabulation analysis and independent sample t-test. A sample of 307 first year students from the University of the Witwatersrand completed the questionnaire online and were asked to indicate the school they attended before they enroll to university. Only the Black African participants were found to have attended low quintile schools (quintile 1 to 3), therefore, only this group was used in the analyses relating to school background. Unexpectedly, the relationship between school background and adaptation to university using the SACQ was found not to be significant. However, the results indicated that the acculturation orientation of students from high and low quintile schools differed. The results also indicated that the students’ academic performance varied according to their acculturation orientation and school background. Recommendations made from the study include; creating a specific tailored programme for tertiary students from two different school quintile backgrounds, educating and implementing ways of teaching that encourage healthy acculturation and acceptance of diversity and frequent pre-exposure of the university life, most especially for students from disadvantaged school background
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirement for the degree of Master of Arts in Industrial/Organisational Psychology, 2021